COVID-19 DISSEMINATION ASSESSMENT THROUGH NATURAL VENTILATION IN HOSPITAL PATIENT ROOM BY CFD ANALYSIS - ghasempourabadi, mohammadhossein; Hassanzadeh, Hossein; Shahrigharahkoshan, Shaghayegh; taraz, masoume (Universitas Pendidikan Indonesia, 2021)
This paper studies the effect of natural ventilation on the spread of the COVID-19 virus from a patient room to an adjacent room with the help of airflow. The importance of this study is since COVID-19 virus contamination can easily transfer with the airflow from one room to the next room or adjacent corridor. This paper aims to determine the effect of natural ventilation on the contamination of the spaces next to the COVID-19 patients’ room.For this evaluation, we have used mechanical modelling and CFD simulation to evaluate the effect of natural ventilation on the transmission of COVID-19 with the airflow from a contaminated space to a clean space. During this study, we have calibrated the CFD model using one actual case, that was studied in a wind tunnel, and verified the modified model with the actual existing case. The simulated CFD model showed a reasonable accuracy for the prediction of ventilation in indoor spaces.Results showing the room geometries with air inlet/outlet that positioned at either bottom or top of the room will result in less COVID contamination dissemination through natural ventilation. In addition, in case of having the inlet/outlet in middle and positioning face to face and as well in the case of having max natural air velocity, the maximum contamination will exhaust from the space.